Device-to-Device Communications in Cloud, MANET and Internet of Things Integrated Architecture - Tanweer Alam (Universitas Airlangga, 2020)
Background: The wireless networks make it easier for users to connect with each other in the sense of the Internet of Things (IoT) system. The cloud and MANET convergence offer the services for cloud access within MANET of devices connected.Objective: The main objective of this research is to establish a cloud-based ad-hoc network architecture for the communication among smart devices under the 5G based Internet of Things architecture.Methods: The methods are applied to discover the smart devices using probability-based model, hidden Markov model and gradient-based model.Results: A cloud-MANET architecture of the smart device is constructed with cloud and MANET computation. The framework allows MANET users to access and deliver cloud services through their connected devices, where all simulations, error handling, and resource management are implemented.Conclusion: The MANET service has been launched as well as linked to the cloud by the mobile device. The author used the amazon cloud storage service. This research produces a conceptual model that is based on the ubiquitous method. It is shown the success in this area and expectations for future scope.